1992
DOI: 10.1302/0301-620x.74b6.1447243
|View full text |Cite
|
Sign up to set email alerts
|

Systemic distribution of wear debris after hip replacement. A cause for concern?

Abstract: The production of particulate wear debris is a recognised complication of joint arthroplasty, but interest has concentrated on local tissue reactions and a possible association with implant loosening. The fate of wear products in the body remains unknown, although some of the metals used in the construction of orthopaedic implants are known to have toxic and oncogenic properties. We report histological and electron-microscopic evidence from two cases which shows that metallic debris can be identified in the ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(60 citation statements)
references
References 0 publications
1
56
1
2
Order By: Relevance
“…However, as previously mentioned, this does not exclude the presence of submicron particles. Metal particles from patients with arthroplasties have been demonstrated with electron microscopy and mass spectrometry in tissues such as bone marrow, spleen, liver, lung and kidney (Langkamer et al 1992, Case et al 1994. Widespread dissemination of wear debris should be taken seriously.…”
Section: Discussionmentioning
confidence: 99%
“…However, as previously mentioned, this does not exclude the presence of submicron particles. Metal particles from patients with arthroplasties have been demonstrated with electron microscopy and mass spectrometry in tissues such as bone marrow, spleen, liver, lung and kidney (Langkamer et al 1992, Case et al 1994. Widespread dissemination of wear debris should be taken seriously.…”
Section: Discussionmentioning
confidence: 99%
“…The authors associated the presence of titanium particles in a patient to granulomatous reactions and hepatomegalia. Various studies have reported the presence of macrophages related to failed prostheses, both orthopedic and dental (Adya et al, 2005;Langkamer et al, 1992;Lee et al, 1992;Olmedo et al, 2003;Urban et al, 2002).…”
Section: Clinical Implications Of Corrosionmentioning
confidence: 99%
“…In addition, concentrations of Co and Cr ions in hip aspirate (> 10 µM) have been found to be higher than circulating levels (De Smet et al, 2008;Kwon et al, 2009). Furthermore, post-mortem studies have shown extremely high levels of metals (> 100 µM) in organs and tissues after traditional metal hip arthroplasty, for example in the liver, lymph nodes, and spleen (Langkamer et al, 1992;Case et al, 1994).…”
Section: Original Articlementioning
confidence: 99%